Misconceptions and myhts about cognitive-behavioral therapy among psychiatrists and psychiatry residents [Psikiyatristler ve psikiyatri asistanlarında bilişsel-davranışçı terapi hakkında mitler ve yanlış bilinenler] - (:unkn) unknown (Cukurova University, Faculty of Medicine, 2014)
Objective: Despite its well established efficacy for various psychological problems, cognitive-behavioral therapy (CBT) is surrounded by numerous false beliefs and myths. Some of these myths are not only common in clients, but are also shared by clinicians working in the area of psychiatry. Therefore, this study primarily aimed to detect the myths related to CBT that are common among Turkish psychiatrists and psychiatry residents in comparison with a sample of non-Turkish European psychiatry residents. Methods: A questionnaire was developed by the researchers to detect the participants’ opinions on the following variables: personal interest in psychotherapy, CBT training available in the institution they work at and formal training through courses, the effectiveness of CBT on various psychiatric disorders and some of the common myths and misconceptions about CBT. A total of 140 partici-pants -73 psychiatry trainees, 33 young psychiatrists from Turkey and 34 members of The European Federation of Psychiatric Trainees (EFPT) from different European countries completed the questionnaire. Results: The data revealed that only 32.1% of participants have education/training on CBT in their psychiatry training programs and only 2.9% of the whole study group rated CBT training in their institution as ‘sufficient’. 40.7% of participants (n=57) reported that CBT is the type of psychotherapy they are most interested in. CBT was seen as a treatment primarily for anxiety disorders but not in more severe disorders such as schizophrenia, bipolar and personality disorders. More than half of the participants have totally or partially agreed some CBT myths such as being superficial, ignoring emotions or an approach that only provides symptomatic relief. Conclusions: The findings of the study indicate the need to evaluate alternative and better ways of promoting CBT in order to reduce misunderstandings and improve good practice amongst professionals working in the area of psychiatry. The findings indicate the need to promote CBT and increase awareness for possible misconceptions and myths that have grown up around CBT. This will help reduce myths and misconceptions about CBT. Therefore it will also improve good practice amongst psycho-therapy professionals and motivate purchasers and clients to demand help for a wide range of psychological problems that CBT may be effective. © 2014, Cukurova University, Faculty of Medicine. All rights reserved.
Keywords: CBT; Cognitive behavioral therapy; Myths; Psychotherapy; Supervision; Training